2018
DOI: 10.1002/jcp.27607
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin attenuates myocardial cell apoptosis following myocardial ischemia‐reperfusion injury through inhibition of miR‐146a‐5p expression

Abstract: The aim of the current study was to investigate the effects and the underlying mechanisms of troxerutin on myocardial cell apoptosis during ischemia‐reperfusion (I/R) injury. Hypoxia/reoxygenation (H/R) model in neonatal rat cardiomyocytes, and I/R model in rats, were established following troxerutin preconditioning. The quantitative real‐time polymerase chain reaction analysis was performed to examine the messenger RNA miR‐146a‐5p expression in cardiomyocytes and myocardial tissues. Hemodynamic parameters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Suppression of miR-146a-5p in mesenchymal stem cells (MSCs) inhibited their proliferation but promoted their migration, suggesting that miR-146a-5p is crucial to uncouple the direct effects of proliferation and motility of MSCs [32]. Our study together with several previous studies [16, 30] suggested that miR-146a-5p also could mediate IH-induced injury in H9c2 cells.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Suppression of miR-146a-5p in mesenchymal stem cells (MSCs) inhibited their proliferation but promoted their migration, suggesting that miR-146a-5p is crucial to uncouple the direct effects of proliferation and motility of MSCs [32]. Our study together with several previous studies [16, 30] suggested that miR-146a-5p also could mediate IH-induced injury in H9c2 cells.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, miR-146a-5p has been verified as a crucial regulator in the development of numerous cancers such as breast cancer [13], prostate cancer [14], and gastric cancer [15]. Furthermore, miR-146a-5p was upregulated in the myocardial hypoxia/reoxygenation (H/R) cell model and rat model of ischemia/reperfusion (I/R), while troxerutin could exert cardioprotective effects on H/R cells and I/R-injured rats by downregulation of miR-146a-5p [16]. However, the effects and modulatory mechanism of miR-146a-5p in protecting cardiomyocytes from IH-induced injury have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this negative effect of SFN was maintained in the S. aureus-infected Nrf2 -/-BMdM. The expression levels of miR-142-5p and miR-146a-5p have been associated with cell apoptosis (26,27). Therefore, the effects of SFN on the levels of these miRNAs were examined.…”
Section: Sfn Affects Intracellular S Aureus Survival and Cell Apoptosismentioning
confidence: 99%
“…However, one must not overlook their pro-survival effects that could elicit, for example, an adverse fibrotic response or a worsened diabetic retinopathy [108,118,119,120,121]. Indeed, this becomes important since it was very recently shown that downregulating miR-146a-5p may be needed in alleviating I/R injury [122]. Therefore, additional research is still required to better elaborate on the effects of individual and synergetic application of these miRNAs.…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%